Inventory inaccuracies in the wholesale supply chain - Rekik, Yacine (International journal of production economics, 2011)
The inventory level shown in the Information System contrary to popular belief and assumptions in most academic papers and inspite of the considerable amounts invested in information technology, is often inaccurate.The inventory inaccuracy occurs when the inventory shown int he Information System is not in agreement with the actually available inventory. In this paper,we first describe the major factors generating inventory inaccuracy. Then,we provide situations permitting to manage an inventory system subject to errors. We provide a general framework permitting to model the inventory inaccuracy issue. In particular,we link the inaccuracy issue with the well known random yield problem.The shown link permits us to derive the optimal ordering policy of an inventory framework where demand satisfaction is done based on the inventory records(which are subject to inaccuracies). We also propose an analysis permitting to show the added value of an advanced identification system such as the RFID technology.